Studi Pemahaman Keselamatan Berkendaraan (Safety Riding) Mahasiswa Program Studi Pendidikan Teknik Otomotif - Widiyatmoko Widiyatmoko; Arif Susanto; Mike Elly Anitasari (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
A traffic accident is an unexpected and unintentional road event involving a vehicle with or without other road users which results in human casualties and property loss. Youth and productive age are one of the highest groups who become victims of traffic accidents. Therefore, safety riding is a program to prevent and reduce the number of traffic accidents. This research aims to determine the understanding of driving safety (safety riding) among automotive engineering education students at Muhammadiyah University of Puworejo. This research is a descriptive study with a cross sectional study design. This research was conducted from August - December 2023. The population in this research were students from the UMP automotive engineering education study program, from whom 160 research samples were then taken as respondents using random sampling. Data were analyzed using quantitative descriptive analysis. The research results show that students' understanding of the principles of road safety is in the high category, namely 52%. This means that students in the Automotive Engineering Education study program at Muhammadiyah University, Purworejo, have a good understanding of the principles of safety riding.